Reforms in France: When Competition and Cooperation Clash - Musselin, Christine (International Higher Education, 2019)
France has experienced two major waves of reforms in the past fifteen years. The first one enhanced cooperation at the local level and the second increased the level of competition. This paper describes these reforms and analyses how they interfered one with another.